2019
DOI: 10.3389/fmicb.2019.01527
|View full text |Cite
|
Sign up to set email alerts
|

The Type III Secretion System (T3SS)-Translocon of Atypical Enteropathogenic Escherichia coli (aEPEC) Can Mediate Adherence

Abstract: The intimin protein is the major adhesin involved in the intimate adherence of atypical enteropathogenic Escherichia coli (aEPEC) strains to epithelial cells, but little is known about the structures involved in their early colonization process. A previous study demonstrated that the type III secretion system (T3SS) plays an additional role in the adherence of an Escherichia albertii strain. Therefore, we assumed that the T3SS could be related to the adherence effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…These data suggested that this specific cluster could harbor strains with an attenuated diarrheagenic phenotype, which is reinforced by the few FAS positive signals produced by UPEC 252 in HeLa cells mentioned above. However, more studies are necessary to confirm this hypothesis because ST10 bears other EPEC clusters in which several pathogenic EPEC strains that had been isolated from diarrhea were detected (Ferdous et al, 2016 ; Arais et al, 2018 ; Santos et al, 2019 ). Besides the EPEC related genes, other virulence factors were identified in the genome of UPEC 252, among which genes that are involved in bacterial adherence to host cells, like E. coli laminin-binding fimbriae (ELF), E. coli common pilus (ECP), and Type 1 fimbriae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These data suggested that this specific cluster could harbor strains with an attenuated diarrheagenic phenotype, which is reinforced by the few FAS positive signals produced by UPEC 252 in HeLa cells mentioned above. However, more studies are necessary to confirm this hypothesis because ST10 bears other EPEC clusters in which several pathogenic EPEC strains that had been isolated from diarrhea were detected (Ferdous et al, 2016 ; Arais et al, 2018 ; Santos et al, 2019 ). Besides the EPEC related genes, other virulence factors were identified in the genome of UPEC 252, among which genes that are involved in bacterial adherence to host cells, like E. coli laminin-binding fimbriae (ELF), E. coli common pilus (ECP), and Type 1 fimbriae.…”
Section: Discussionmentioning
confidence: 99%
“…Secreted proteins were extracted as described by Zarivach et al ( 2007 ), and an immunoblotting assay using an anti-EspB primary antibody (Guirro et al, 2013 ) and anti-rabbit secondary IgG antibody (whole molecule)-Peroxidase (Sigma, Saint Louis, EUA) was employed to evaluate the ability of UPEC 252 to produce T3SS. A protein extract from the typical EPEC prototype strain E2348/69 was used as a positive control (Santos et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…and bacterial count, was used as inoculum. After incubation and washes, the cells were lysed by adding 1 mL of sterile bi-distilled water, which was recovered, diluted, and plated onto MacConkey agar for quantification as previously described [77]. The assays were performed in biological duplicates and experimental triplicates, and the data were expressed as the mean and standard error of the mean (SEM).…”
Section: Adherence Assays In Hela Caco-2 and T24 Cellsmentioning
confidence: 99%